Optimization by Integration: A Corporate Governance and Human Resource Management Dimension - Oyewunmi, Olabode Adeleke; Osibanjo, Omotayo Adewale; Falola, Hezekiah Oluwabusayo; Olujobi, Olusola Joshua (International Review of Management and Marketing, 2017)
Contemporary business entities that are keen to achieve measurable growth can no longer rely on inflexible corporate management frameworks for running their affairs. This viewpoint is adduced in the light of the emergence and re-emergence of unpredictable and likewise complex operating contexts. Notwithstanding the connected legal, financial, economic and social issues; business concerns must devise innovative ways to sustain holistic performance levels. Moreover, corporate and regulatory interests must collaborate to effectively mitigate corporate failures attributable to various business concerns. In furtherance of the debate on the nexus between corporate governance and human resource management, this paper presented a conceptual model that aggregates specific aspects of business processes that synergizes both concepts. Practical perspectives on the interrelatedness between corporate governance and human resource management provide a veritable basis to explore the theme of this paper. The paper opined that an appropriate balance must be achieved with regards to identifiable and fundamental aspects of the corporate structure and process. It was recommended that a diverse model of corporate integration enhances the functionalities of the corporate entity; facilitates optimization processes, thereby contributing to long term sustainability and growth. The central role of human actors in the governance of business entities is also duly emphasized, as this viewpoint underlies the essence of integrating the two concepts in general and specific terms. Keywords: Corporate Governance, Human Resource Management, Corporate Strategy JEL Classifications: M12, M21, M54